Oxidative and reductive cyclization in stiff dithienylethenes - Kleinwächter, Michael; Teichmann, Ellen; Grubert, Lutz; Herder, Martin; Hecht, Stefan (Beilstein Journal of Organic Chemistry, 2018)
The electrochemical behavior of stiff dithienylethenes, undergoing double bond isomerization in addition to ring-closure, has been investigated. Electrochromism was observed in almost all cases, with the major pathway being the oxidatively induced cyclization of the open isomers. The influence of the ring size (to lock the reactive antiparallel conformation) as well as substituents (to modulate the redox potential) on the electrocyclization was examined. In the series of derivatives with 6-membered rings, both the E- and the Z-isomer convert to the closed isomer, whereas for the 7-membered rings no cyclization from the E-isomer was observed. For both stiff and normal dithienylethenes bearing benzonitrile substituents an additional and rare reductive electrocyclization was observed. The mechanism underlying both observed electrocyclization pathways has been elucidated.
Keywords: diarylethenes; electrochromism; molecular switches; (spectro)electrochemistry

(untitled) - Irie, M.; Mohri, M. (J. Org. Chem., 1988)

(untitled) - Nakamura, S.; Irie, M. (J. Org. Chem., 1988)

(untitled) - Irie, M. (Chem. Rev., 2000)

(untitled) - Irie, M.; Fukaminato, T.; Matsuda, K.; Kobatake, S. (Chem. Rev., 2014)

(untitled) - Herder, M.; Utecht, M.; Manicke, N.; Grubert, L.; Pätzel, M.; Saalfrank, P.; Hecht, S. (Chem. Sci., 2013)

(untitled) - Peters, A.; Branda, N. R. (Chem. Commun., 2003)

(untitled) - Browne, W. R.; de Jong, J. J. D.; Kudernac, T.; Walko, M.; Lucas, L. N.; Uchida, K.; van Esch, J. H.; Feringa, B. L. (Chem. – Eur. J., 2005)

(untitled) - Browne, W. R.; de Jong, J. J. D.; Kudernac, T.; Walko, M.; Lucas, L. N.; Uchida, K.; van Esch, J. H.; Feringa, B. L. (Chem. – Eur. J., 2005)

(untitled) - Liu, Y.; Lagrost, C.; Costuas, K.; Tchouar, N.; Le Bozec, H.; Rigaut, S. (Chem. Commun., 2008)

(untitled) - He, B.; Wenger, O. S. (J. Am. Chem. Soc., 2011)

(untitled) - Staykov, A.; Areephong, J.; Browne, W. R.; Feringa, B. L.; Yoshizawa, K. (ACS Nano, 2011)

(untitled) - Harvey, E. C.; Areephong, J.; Cafolla, A. A.; Long, C.; Browne, W. R.; Feringa, B. L.; Pryce, M. T. (Organometallics, 2014)

(untitled) - Meng, F.; Hervault, Y.-M.; Shao, Q.; Hu, B.; Norel, L.; Rigaut, S.; Chen, X. (Nat. Commun., 2014)

(untitled) - Koshido, T.; Kawai, T.; Yoshino, K. (J. Phys. Chem., 1995)

(untitled) - Peters, A.; Branda, N. R. (J. Am. Chem. Soc., 2003)

(untitled) - Zhou, X.-H.; Zhang, F.-S.; Yuan, P.; Sun, F.; Pu, S.-Z.; Zhao, F.-Q.; Tung, C.-H. (Chem. Lett., 2004)

(untitled) - Nakashima, T.; Kajiki, Y.; Fukumoto, S.; Taguchi, M.; Nagao, S.; Hirota, S.; Kawai, T. (J. Am. Chem. Soc., 2012)

(untitled) - Lee, S.; You, Y.; Ohkubo, K.; Fukuzumi, S.; Nam, W. (Org. Lett., 2012)

(untitled) - Massaad, J.; Micheau, J.-C.; Coudret, C.; Serpentini, C. L.; Guirado, G. (Chem. – Eur. J., 2013)

(untitled) - Lee, S.; You, Y.; Ohkubo, K.; Fukuzumi, S.; Nam, W. (Chem. Sci., 2014)

(untitled) - Calupitan, J. P.; Nakashima, T.; Hashimoto, Y.; Kawai, T. (Chem. – Eur. J., 2016)

(untitled) - Moriyama, Y.; Matsuda, K.; Tanifuji, N.; Irie, S.; Irie, M. (Org. Lett., 2005)

(untitled) - Guirado, G.; Coudret, C.; Hliwa, M.; Launay, J.-P. (J. Phys. Chem. B, 2005)

(untitled) - Coudret, C.; Guirado, G.; Hortholary, C.; Launay, J.-P.; Battaglini, N.; Klein, H.; Dumas, P. (Mol. Cryst. Liq. Cryst., 2005)

(untitled) - Yuan, N.; Zhang, Z.; Wang, X.; Wang, X. (Chem. Commun., 2015)

(untitled) - Zhang, Z.-X.; Wang, P.-X.; Bai, F.-Q.; Kong, C.-P.; Zhang, H.-X. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Gorodetsky, B.; Samachetty, H. D.; Donkers, R. L.; Workentin, M. S.; Branda, N. R. (Angew. Chem., 2004)

(untitled) - Gorodetsky, B.; Branda, N. R. (Adv. Funct. Mater., 2007)

(untitled) - Léaustic, A.; Anxolabéhère-Mallart, E.; Maurel, F.; Midelton, S.; Guillot, R.; Métivier, R.; Nakatani, K.; Yu, P. (Chem. – Eur. J., 2011)

(untitled) - Ogawa, K.; Suzuki, H.; Futakami, M. (J. Chem. Soc., Perkin Trans. 2, 1988)

(untitled) - Oelgemöller, M.; Brem, B.; Frank, R.; Schneider, S.; Lenoir, D.; Hertkorn, N.; Origane, Y.; Lemmen, P.; Lex, J.; Inoue, Y. (J. Chem. Soc., Perkin Trans. 2, 2002)

(untitled) - Oelgemöller, M.; Frank, R.; Lemmen, P.; Lenoir, D.; Lex, J.; Inoue, Y. (Tetrahedron, 2012)

(untitled) - Lewis, F. D.; Petisce, J. R.; Oxman, J. D.; Nepras, M. J. (J. Am. Chem. Soc., 1985)

(untitled) - Majima, T.; Tojo, S.; Ishida, A.; Takamuku, S. (J. Org. Chem., 1996)

(untitled) - Bragadin, M.; Cescon, P.; Berlin, A.; Sannicolò, F. (Makromol. Chem., 1987)

(untitled) - Onoda, M.; Iwasa, T.; Kawai, T.; Yoshino, K. (J. Phys. Soc. Jpn., 1991)

(untitled) - Benincori, T.; Brenna, E.; Sannicolò, F.; Trimarco, L.; Schiavon, G.; Zecchin, S.; Zotti, G. (Macromol. Chem. Phys., 1996)

(untitled) - Irie, M.; Lifka, T.; Uchida, K.; Kobatake, S.; Shindo, Y. (Chem. Commun., 1999)

(untitled) - Herder, M.; Schmidt, B. M.; Grubert, L.; Pätzel, M.; Schwarz, J.; Hecht, S. (J. Am. Chem. Soc., 2015)

(untitled) - Herder, M.; Eisenreich, F.; Bonasera, A.; Grafl, A.; Grubert, L.; Pätzel, M.; Schwarz, J.; Hecht, S. (Chem. – Eur. J., 2017)

(untitled) - Berberich, M.; Würthner, F. (Asian J. Org. Chem., 2013)

(untitled) - Liu, G.; Pu, S. Z.; Zheng, C. H.; Le, Z. G.; Luo, M. B. (Phys. Scr., 2007)

(untitled) - Goulet-Hanssens, A.; Utecht, M.; Mutruc, D.; Titov, E.; Schwarz, J.; Grubert, L.; Bléger, D.; Saalfrank, P.; Hecht, S. (J. Am. Chem. Soc., 2017)

(untitled) - Goulet-Hanssens, A.; Rietze, C.; Titov, E.; Abdullahu, L.; Grubert, L.; Saalfrank, P.; Hecht, S. (Chem, 2018)

(untitled) - Matsuda, K.; Yokojima, S.; Moriyama, Y.; Nakamura, S.; Irie, M. (Chem. Lett., 2006)

(untitled) - Logtenberg, H.; Browne, W. R. (Org. Biomol. Chem., 2013)

(untitled) - Testa, A. C.; Reinmuth, W. H. (Anal. Chem., 1961)

(untitled) - Abdul-Rahim, O.; Simonov, A. N.; Boas, J. F.; Rüther, T.; Collins, D. J.; Perlmutter, P.; Bond, A. M. (J. Phys. Chem. B, 2014)